Cognitive motivation and its relationship to cognitive abilities according to Bloom's Taxonomy of Educational Philosophy in the subject of Sports Psychology among students of the College of Physical Education and Sports Sciences / Al-Qadisiyah University: Motivasi kognitif dan hubungannya dengan kemampuan kognitif berdasarkan Taksonomi Filsafat Pendidikan Bloom dalam mata kuliah Psikologi Olahraga di kalangan mahasiswa Fakultas Pendidikan Jasmani dan Ilmu Olahraga / Universitas Al-Qadisiyah - Ghyaidh, Hussein Rashid (Indonesian Journal of Education Methods Development, 2026)
General Background: Cognitive motivation plays a central role in shaping students’ engagement and learning outcomes within educational environments. Specific Background: In educational psychology, measuring cognitive motivation is essential for understanding how students think, learn, and respond to instructional strategies. Knowledge Gap: Despite extensive theoretical discussions, there is still a need for structured measurement approaches that capture cognitive motivation accurately within specific student populations. Aims: This study aims to measure cognitive motivation among students and examine its characteristics using established psychological assessment methods. Results: The findings indicate that cognitive motivation can be systematically assessed through validated instruments, revealing variations in students’ levels and patterns of engagement in learning activities. The analysis highlights meaningful differences in responses, reflecting diverse cognitive tendencies among participants. Novelty: The study applies structured measurement tools within a defined educational context, providing empirical insight into cognitive motivation assessment. Implications: The results contribute to educational practice by offering a basis for improving instructional strategies and supporting student learning through a better understanding of motivational factors. Keywords: Cognitive Motivation, Educational Psychology, Student Assessment, Learning Behavior, Psychological Measurement Key Findings Highlights Measurement framework identifies variation in student engagement patterns Assessment results show distinct motivational tendencies across participants Findings support structured evaluation in academic settings